Analysis of the Capital City of the Archipelago (IKN) in the Perspective of the Future Climate for the Period 2023-2050 using the Data of the SSP 2.0-4.5 - Anam, Aqasha Raechan; Dewi, Bella Puspita; Purnama, Fahmi Yuwan (Universitas Pendidikan Indonesia, 2024)
The Archipelago's Capital City Region (IKN) is a candidate for Indonesia's new capital city. It requires in-depth research across all relevant sectors to ensure the comfort of the people of Indonesia. Numerous studies have been conducted in various fields, including social, cultural, political, economic, and others. However, no study has provided a climate-based perspective on IKN compared to the others. Extreme climate indices calculation for the IKN region used the latest projection data, SSP, and statistical analysis techniques via R programming. According to 18 extreme climate indices, the IKN region is expected to experience an increasing trend in both temperature and precipitation indices until 2050. The temperature index that experienced the most significant increase is T90p, while the rainfall index is RX1day. In the IKN region, there is a difference of about 300 days between wet days (CWD) and dry days (CDD), with 350 days being wet and 35 days being dry. Spatial projection analysis has revealed an increase in CWD values in most of the IKN area during the rainy season and a decrease in CWD values during the dry season.